How to prepare a statement of cash flow by the direct method (GEON Journal (Management, Organizations and Business), 2018)
The article was created with the objective of demonstrating the way to develop the cash flow statement by the direct method, for which a focus study of the mix is ​​offered, based on a review of the scientific and documentary literature, consulted in indexed databases such as Scielo, Procuex, Ciencie Sdirect, Elsevier, among others, which compile journals of academic and scientific recognition. The results are presented step by step, where the results of the cash operation, investment and financing are required, for which the results that allow a greater compression are presented. Among other things, it is concluded that the direct method allows reaching the objective of cash flow statements.
Keywords: Accounting; financial statements; cash flow